2019
DOI: 10.1177/1753193419875945
|View full text |Cite
|
Sign up to set email alerts
|

Decompression for recurrent carpal tunnel syndrome provides significant functional improvement and patient satisfaction

Abstract: This prospective single-centre study describes the functional outcomes, satisfaction and health-related quality of life after open revision carpal tunnel decompression for recurrent carpal tunnel syndrome. The QuickDASH, patient satisfaction and EuroQol-5 dimensions questionnaires were collected preoperatively and postoperatively over a 5-year period (2013–2018). The median time to revision was 13.3 years (range 3.9–35.4 years; interquartile range 7.2–15.9 years). Outcomes were available for 14 hands in 13 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Detailed characteristics are presented in Online Tables S2 and S3. Studies were grouped by type of intervention: open revision (CTRopen, n ¼ 6: Cobb et al, 1996;Impelmans et al, 2001;Kluemper et al, 2019;Stirling et al, 2020;Unglaub et al, 2008;Wadstroem and Nigst, 1986), open revision with flap coverage (CTR flap, n ¼ 11: Craft et al, 2007;Dahlin et al, 2002;Fusetti et al, 2009;Karthik et al, 2012;Mathoulin et al, 2000;Rose et al, 1991;Strickland et al, 1996;Stutz et al, 2008;Sun et al, 2020;Vogelin et al, 2008;Wichelhaus et al, 2015) or implant (CTR-implant, n ¼ 3: Bilasy et al, 2012;Carmona et al, 2019;Nassar and Atiyya, 2014). Most studies in the CTR-flap group used the hypothenar fat pad flap (n ¼ 7).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics are presented in Online Tables S2 and S3. Studies were grouped by type of intervention: open revision (CTRopen, n ¼ 6: Cobb et al, 1996;Impelmans et al, 2001;Kluemper et al, 2019;Stirling et al, 2020;Unglaub et al, 2008;Wadstroem and Nigst, 1986), open revision with flap coverage (CTR flap, n ¼ 11: Craft et al, 2007;Dahlin et al, 2002;Fusetti et al, 2009;Karthik et al, 2012;Mathoulin et al, 2000;Rose et al, 1991;Strickland et al, 1996;Stutz et al, 2008;Sun et al, 2020;Vogelin et al, 2008;Wichelhaus et al, 2015) or implant (CTR-implant, n ¼ 3: Bilasy et al, 2012;Carmona et al, 2019;Nassar and Atiyya, 2014). Most studies in the CTR-flap group used the hypothenar fat pad flap (n ¼ 7).…”
Section: Resultsmentioning
confidence: 99%
“…In a homogenous case series involving 13 patients with recurrent symptoms who underwent surgery using a similar technique, Duclos and Sokolow [23] reported a symptom(s) disappearance rate of 92% over an average of 27.5-month follow-up. More recently, over an average of 20-month follow-up of 14 patients with recurrent CTS treated with a similar technique, other authors reported a statistically significant improvement in QuickDASH scores, improvement in mean EuroQol 5-Dimension 3-Level (EQ-5D-5L) general health questionnaire scores, satisfaction among 13 patients, a net promoter score of 85, and lack of complications [11]. Neither of these studies, however, assessed the speed of symptom-(s) recovery, which was the focus of the present investigation.…”
Section: Discussionmentioning
confidence: 98%
“…ported in the literature, ranging from simple release to those using complicated flaps and interposing tissue [6,8,10,11]. These perioperative challenges affecting patient consultation are also encountered when opting for the simplest techniquenamely, repeated decompression without added proceduresdue to the limited number of studies exclusively addressing its outcomes [6,12].…”
Section: Standard Incision and Median Nerve External Neurolysis For R...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, revision surgery is required in in 5-10% of patients (Westenberg et al, 2020). Repeated decompression with or without external or internal neurolysis has been reported as the standard technique (Stirling et al, 2020;Unglaub et al, 2008). In this situation, we now carry out preoperative bilateral ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%